REDESIGN OF PURWOKERTO WAGE MARKET WITH BIOCLIMATIC ARCHITECTURE APPROACH - Sulistiyo, Jafar Imam; Santoso, Eko Budi; Setiawan, Moch Fathoni; Wicaksono, Dimas (Canopy: Journal of Architecture, 2024)
Purwokerto Wage Market is the main market that is the center of trade in the Purwokerto area. Circulation in the market is one of the problems that need to be overcome and also the lack of openings causes the temperature in the market to be quite high during the day. From the data obtained, the temperature in the city of Purwokerto ranges from 21.4°C – 29°C. In addition, waste management that is not optimal causes the atmosphere to be less comfortable for both traders and market visitors. The number of informal traders who occupy areas that are not specifically for selling is one of the problems that must be solved. To overcome these problems, it is necessary to plan and design the market with a bioclimatic architecture approach that pays attention to the condition of the building and the environment. The analysis was carried out which was divided into several approaches, namely, functional approach, contextual approach, structural approach, performance approach, and architectural approach. The design was then carried out thermal tests using thermometers and digital anemometers in the morning and afternoon with temperature results at 30°C – 30.8°C. From the results of data collection and data analysis, a design plan for the main market building was obtained that was in accordance with the needs of its users. From the results of the study, it can be concluded that the application of the bioclimatic concept to buildings and site areas is a hallway and on the façade of the building in the form of secondary skin, vertical garden, dynamic façade which protects the building from direct exposure to sunlight. Then the rainwater collector is placed in the central area and as a vew in the building itself. The design that has been designed can be a reference in the redesign of the Purwokerto Wage Market building in improving and overcoming existing problems.